Papyrus 72 and the Bodmer Miscellaneous Codex : a study of the dynamics of early Christian identity formation - Kok, Jacobus (Kobus) (University of Pretoria, 2023)
Dissertation (MTh (New Testament Studies))--University of Pretoria, 2023.